Jesus Christ message to all nations. - Jeffs, Warren, 1955-; Fundamentalist Church of Jesus Christ of Latter Day Saints ([Colorado City, Ariz.] : Fundamentalist Church of Jesus Christ of Latter Day Saints, 2012)
Item contains a compendium of prophecies delivered to Warren S. Jeffs by Jesus Christ during 2010-2012, principally at Palestine, Texas.
President Warren S. Jeffs, Mouthpiece of God, Jesus Christ, Author.'
Keywords: Fundamentalist Church of Jesus Christ of Latter Day Saints; Prophecy; Eschatology